2019
DOI: 10.1016/j.expneurol.2018.12.006
|View full text |Cite
|
Sign up to set email alerts
|

KU-596 decreases mitochondrial superoxide and improves bioenergetics following downregulation of manganese superoxide dismutase in diabetic sensory neurons

Abstract: Neuronal mitochondrial dysfunction and oxidative stress are key pathophysiologic mechanisms of diabetic peripheral neuropathy (DPN). KU-596 is a small molecule modulator of heat shock protein 90 (Hsp90) that can reverse clinically relevant measures of DPN in diabetic animal models. Mechanistically, drug efficacy requires Hsp70 and correlates with improving mitochondrial maximal respiratory capacity (MRC) and decreasing oxidative stress in diabetic sensory neurons. The goal of this study was to determine if ex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Weight was evaluated every week. Animals that exhibited blood glucose levels > 16.7 mmol/L within 1 week after the completion of STZ injection were considered diabetic and were included in the study; these animals showed progression to neuropathy-like symptoms and were tested behaviourally after 6 weeks [29,30].…”
Section: Animals and Treatmentmentioning
confidence: 99%
“…Weight was evaluated every week. Animals that exhibited blood glucose levels > 16.7 mmol/L within 1 week after the completion of STZ injection were considered diabetic and were included in the study; these animals showed progression to neuropathy-like symptoms and were tested behaviourally after 6 weeks [29,30].…”
Section: Animals and Treatmentmentioning
confidence: 99%
“…We have shown that 8 weeks of KU-596 therapy reversed a pre-existing mechanical and thermal hypoalgesia, increased nerve conduction velocity, and improved deficits in mtBE that develop by 16 weeks of diabetes in C57Bl/6 mice. , To assess the effect of diabetes and KU-596 treatment on mitophagy, male and female 6–8 week-old MQC mice were rendered diabetic with two intraperitoneal injections of 100 mg/kg streptozotocin (STZ) given on consecutive days. After 8 weeks of diabetes, mice were administered 1 mg/kg KU-596 or Captisol (drug vehicle) by daily oral gavage for an additional 8 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the drug did not improve MRC and SRC in neurons from diabetic MQC × Hsp70 KO mice. We have previously observed that nondiabetic Hsp70 KO neurons treated with KU-596 had a higher MRC and SRC than vehicle-treated nondiabetic neurons . Thus, the drug may have some Hsp70-independent effects to improve mtBE in nondiabetic neurons, but improving mtBE in diabetic neurons requires Hsp70 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations